Neuropilin 1 is essential for gastrointestinal smooth muscle contractility and motility in aged mice. - Maiko Yamaji; Marwa Mahmoud; Ian M Evans; Ian C Zachary (PLoS ONE)
Background and aims Neuropilin 1 (NRP1) is a non-tyrosine kinase receptor for vascular endothelial growth factor (VEGF) and class 3 semaphorins, playing a role in angiogenesis and neuronal axon guidance, respectively. NRP1 is expressed in smooth muscle cells (SMC) but the functional role of NRP1 in SMC has not been elucidated. We therefore investigated the biological relevance of NRP1 in SMC in vivo by generating mice with SMC-specific Nrp1 deficiency. Methods Conditional gene targeting generated SMC-specific Nrp1 knockout mice (Nrp1SMKO) in which Cre recombinase is driven by the smooth muscle-specific myosin heavy chain (smMHC) promoter. Results SMC-specific Nrp1 deficiency resulted in a significant reduction in intestinal length by 6 months, and, by 18 months, in severe constipation, and enlargement of the intestine consistent with chronic intestinal pseudo-obstruction. These effects were associated with significant thinning of the intestinal smooth muscle, and decreased intestinal contractility. Expression of contractile proteins was reduced in Nrp1SMKO mice, including the smMHC isoform, SMB, whereas we observed a significant increase in the expression of the small-conductance calcium-activated potassium channel 3 (SK3/KCa2.3), implicated in negative regulation of smooth muscle contraction. Conclusions Nrp1 deficiency in visceral SMC results in adult-onset defects in gastrointestinal contractility and motility and causes a shift to a less contractile SMC phenotype. These findings indicate a new role for Nrp1 in the maintenance of the visceral SMC contractile phenotype required for normal GI motility in aged mice.